The Efficacy of Memory Training Using Montessori Philosophy-based Activities in Mild Dementia Elderly - Nantachai, Gallayaporn; Nivatapan, Rawiwan; Kraisorapong, Kamkeo (Journal of the Psychiatric Association of Thailand, 2013)
Abstract Objective: To compare the memory scores in mild dementia elderly who attended Montessori-based Memory training with the control group who did not. Method: The Solomon four-group design was used to test the memory of the subjects. The subject of the study consisted of 40 elderly at Banbanglamung Social Welfare Development Center for Older Persons. Participants were divided to 2 experimental and 2 control groups by random sampling technique. Mini mental status Exam-Thai 2002 and Thai Geriatric Depression scale were used as a tool in selecting the subject and a tool to differentiate the mild dementia elderly group from the depressed group. The digit span and digit symbol subtests of The Wechsler Intelligence scale were used in memory testing. The data obtained was analyzed by means of descriptive statistics, t-test and one-way ANOVA. Results: The average scores of the digit span and digit symbol of the experimental groups and the controlled groups were significantly different (p<0.05). After 4 weeks of training, the average scores of the experimental groups increased more than that of the controlled group. After training, the average scores of memory of the four groups were significantly indifferent (p<0.05). Digit symbol scores of the experimental groups were higher than of the controlled groups by using LSD method. Conclusion: After memory training, the average scores of the digit span and digit symbol of the experimental groups were significantly higher than the controlled group. This differentce still persisted at the 12th week of training. Therefore, this memory training should be used with the elderly to prevent and delay dementia.